2021
DOI: 10.1108/cfri-03-2021-0049
|View full text |Cite
|
Sign up to set email alerts
|

The impact of green finance, economic growth and energy usage on CO2 emission in Vietnam – a multivariate time series analysis

Abstract: PurposeThis study aims to examine the relationship between green finance, economic growth, renewable energy consumption (energy efficiency), energy import and CO2 emission in Vietnam using multivariate time series analysis.Design/methodology/approachThe data were collected from 1986 to 2018 since Vietnam initiated the economic reforms, namely “Doi Moi” in 1986. The concept and methods of cointegration, Granger causality and error correction model (ECM) were employed to establish the relationship between the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 65 publications
(78 reference statements)
1
18
0
2
Order By: Relevance
“…However, underinvested renewable energy enterprises may not pick up through green financing. It is essential to know that energy efficiency has a direct impact on environmental performance and productivity (Iqbal et al, 2021;Tran, 2021;Awawdeh et al, 2021;Zhang et al, 2021). Sarkar and Singh (2010) argued that financing and implementing energy efficiency projects in developing economies often pose challenges due to inadequate liquidity and the nonavailability of energy-saving technologies.…”
Section: The Role Of Green Finance In Financing Energy Efficiencymentioning
confidence: 99%
See 3 more Smart Citations
“…However, underinvested renewable energy enterprises may not pick up through green financing. It is essential to know that energy efficiency has a direct impact on environmental performance and productivity (Iqbal et al, 2021;Tran, 2021;Awawdeh et al, 2021;Zhang et al, 2021). Sarkar and Singh (2010) argued that financing and implementing energy efficiency projects in developing economies often pose challenges due to inadequate liquidity and the nonavailability of energy-saving technologies.…”
Section: The Role Of Green Finance In Financing Energy Efficiencymentioning
confidence: 99%
“…Another important stride of green finance is that it improves firms' financial efficiency (Yi et al, 2021). However, Tran (2021) shared different opinions on the nexus and affirmed that green finance or investment is insufficient to reduce CO 2 emissions. Cao et al (2021) also found that digital finance positively affects energy and environmental performance through improvement in technical efficiency, while a significant effect is on scale efficiency.…”
Section: The Role Of Green Finance In Financing Energy Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Available papers, including Doni and Johannsdottir (2021), note that in the context of the COVID-19 pandemic and crisis in 2020-2021 the pace of implementation of SDG13 (combating climate change) has slowed down. In particular, this could be due to limited placement opportunities for ESG investments (Gao et al, 2021;Ngo et al, 2021;Tran, 2021).…”
Section: Covid-19 and Green Recoverymentioning
confidence: 99%